Connectedness Among Chilean Adolescents: Factor Analysis of the Hemingway Measure of Adolescent Connectedness La Conectividad Entre Adolescentes Chilenos: Un Análisis Factorial de la Hemingway Measure of Adolescent Connectedness - Benedict T McWhirter; Ellen Hawley McWhirter (Psykhe, 2011)
The construct of connectedness was investigated among 390 Chilean adolescents using the Hemingway Measure of Adolescent Connectedness (Hemingway; Karcher, 2003). Participants were 7th-12th graders at an urban Santiago Catholic school. Results of a principal-axis exploratory factor analysis revealed an 11 factor structure that accounts for 61.92% of total explained variance of adolescent connectedness measured by the Hemingway, similar to results found in the adolescent samples in the United States. Two additional Hemingway subscales (connectedness to siblings and to boyfriend/girlfriend) are also described. Correlations between domains of connectedness and additional data obtained from these adolescents, their parents, and their teachers support the construct validity of the measure in this Chilean sample. Connectedness is an important protective factor among adolescents across many national contexts and the Hemingway is a promising measure for use with Chilean adolescents. Se examinó el constructo conectividad en 390 adolescentes chilenos en un colegio urbano y católico de Santiago. Mediante un análisis factorial exploratorio de la escala Hemingway Measure of Adolescent Connectedness (Hemingway, Karcher, 2003) se observó una estructura de 11 factores que da cuenta de un 61,92% de la varianza explicada de la conectividad de los adolescentes medida por la escala Hemingway, lo cual es muy similar a los resultados obtenidos en muestras de adolescentes estadounidenses. También se describen dos subescalas adicionales (la conectividad con los/las hermanos/as y con los/las pololos/as). Las relaciones entre los factores de conectividad y los datos reportados por los adolescentes, sus padres y profesores contribuyen también a la validez de constructo de la escala en esta muestra chilena. Para los adolescentes de distintos contextos culturales la conectividad es un factor importante de protección y la escala Hemingway es un instrumento de uso prometedor con adolescentes chilenos.